A Case of Physically Abused OCD Patient Who Physically Abused Her own Child - Tuğba AYAZ; Ayşe Gül YILMAZ ÖZPOLAT; Damla YÜCEL; Umut ALTUNÖZ (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
It was suggested that along with genetic factors various psychosocial factors may play a role in the development of Obsessive Compulsive Disorder (OCD). Parents’ childrearing styles and childhood traumatic experiences are among the mostly investigated ones. In literature it was indicated that child rearing styles and childhood traumatic experiences may play a role in the development of OCD. There are studies which show that child rearing styles including excessive protection, critical and rejective are associated with the development of OCD. However, it is still controversial that which child rearing styles lead to the OCD through which mechanisms. Besides, in literature it was shown that emotional traumatic experiences lead to the development of OCD through various factors. In addition, understanding what kind of conflict and problems are reflected by people with OCD diagnosis into the relationship with their children is important in terms of interventions that protect the mental health of the child. In this article, it was aimed to discuss psychosocial factors related to the development of OCD symptoms, by examining a case in detail, who had childhood traumatic experiences and has been raised in an environment where negative parenting styles exist, and who physically abused her own child.